Effect of oral administration of β-glucans derived from Aureobasidium pullulans SM-2001 in model mice and rat with atopic dermatitis-like phenotypes - Kim, In Sung (Food Sci Biotechnol, 2018)
In this study, we investigated the anti-atopic dermatitis (AD) activity of β-glucans derived from Aureobasidium pullulans SM-2001 (βGdAP). βGdAP was orally administered to AD animal models such as vasodilation, allergic pruritus and contact dermatitis. Administration of βGdAP attenuated the amount of Evans blue solution on vasodilation rat. Scratching behaviors, secretion of histamine and ear thickness were significantly (p < 0.05) attenuated in the βGdAP-treated mouse groups. Interestingly, transcriptional expression of T-bet, a transcription factor for Th1 reactions, was increased, but that of GATA-3, a transcription factor for Th2 reactions, was attenuated in the βGdAP-treated groups (p < 0.05). In addition, we found that reduced transcriptional expression of forkhead box P3 and galectin-9, regulators of regulatory T cells, was recovered in the βGdAP-treated groups (p < 0.05). Taken together, these data indicate that administration of βGdAP could effectively attenuate AD-like phenotypes via regulation of Th1/Th2 transcriptional activity and Treg activation.